PENGGUNAAN CLUSTER BOMB PADA KONFLIK BERSENJATA DI SURIAH DITINJAU DARI HUKUM HUMANITER INTERNASIONAL - Zakka Pranggapati Janges (BELLI AC PACIS (Jurnal Hukum Internasional), 2023)
This research aims to analyze the use of banned weapon, cluster bomb, in the armed conflict in Syria by studying the reason why the cluster bomb is banned from the historical, philosophical, and sociological point of view. Additionally, writer also analyze the most effective law enforcing mechanism to address the use of said weapon by Syria government. This is normative research utilizing both primary and secondary legal materials. The legal materials collecting technique is library research equipped with deduction technique to analyze the materials. The result show that the use of cluster bomb is prohibited for the said weapon violate the principle of international humanitarian law such as principle of distinction, proportionality, and military necessity. Hence, the use of cluster bomb by Syria government that cause civilian casualties is a war crime. Furthermore, the most effective law enforcing mechanism to address the use of cluster bomb by Syrian government is through United Nation Security Council Resolution whose content refer the issue to be resolved by ICC.